The Impact of Exposure to Information Technology in Determining Women’s Knowledge of Complication during Pregnancy, Labor, and Postnatal - Nurmawati, Erna; Napitupulu, Joseph Gabriel; Sugiyarto, Teguh (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Indonesian Demographic Health Survey (IDHS) 2012 reveals that Maternal Mortality Ratio (MMR) in Indonesia is 359 per 100,000 live births or increase from 228 per 100.000 live births in 2007. Compared to the other ASEAN countries, the risk of maternal death in Indonesia is also relatively high, 1 in 65 mothers. Some researches depict that maternal death is caused by inadequate care during pregnancy and delivery (labor). This condition is caused by the availability of health facility or improper health seeking behaviors. Considering the crucial role of knowledge to determine people behaviors, this paper is aimed to discuss the impact of information technology to shape people knowledge on maternal health. Subjects and Method: Some variables in Indonesian Health Demographic Survey 2017, identify the subject’s knowledge on danger sign of complication during pregnancy, labor/delivery and postnatal periods. In digitalized era, the knowledge may come from many sources. Therefore, the discussion will focus on the impact of subject’s accessibility and utilization of internet, mobile phone, radio, TV and newspaper in shaping knowledge of maternal health. Results: This study found that women with primary education (OR= 1.57; p < 0.001), did not access the internet (OR= 2.49; p= 0.110); the frequency of accessing the internet for health (OR= 1.94; p= 0.083) increased women's knowledge about dangerous signs during pregnancy. While not reading newspapers (OR= 0.66; p < 0.001); not watching television (OR= 0.66; p<0.001), having or not having television (OR= 0.59; p < 0.001); do not have a mobile phone (OR= 0.64; p<0.001); not having a radio (OR= 0.88; p < 0.001) decreased women's knowledge of the danger signs during pregnancy, but this result was statistically significant. Conclusion: This result reveal that the effectiveness of internet to influence women knowledge on maternal health must be improved because of its potential in this digitalized era and the progressive trend of internet penetration in Indonesia.